KARAKTERISASI EKSTRAK TEH HITAM DAN TINTA CUMI-CUMI SEBAGAI FOTOSENSITISER PADA SEL SURYA BERBASIS PEWARNA TERSENSITISASI - Rachmawati Ningsih; Hastuti Hastuti (Lembaga Penelitian dan Pengembangan Universitas Islam Negeri Maulana Malik Ibrahim Malang., 2012)
One of the alternative energy potential to be developed to overcome energy crisis in the world is an organic solar cells. In this research has been conducted by making a series of Dyes Sensitized Solar Cells (DSSC) using an organic dye from crude extracts of black tea (Camellia sinensis) and ink cuttlefish (Sepia acuelata). Solar cell system consisting of crystalline TiO2, glass conductors, dyes, a electrolyte solution I-/I3- and carbon electrodes. TiO2 crystals were characterized using X-ray diffraction. Crude extracts of black tea and cuttlefish ink absorption wavelength was analyzed using UV-Vis spectrophotometer. The series of solar cells are measured values of voltage and electric current. The results of X-ray diffraction showed that crystalline TiO2 including anatase crystalline phase and a crystal size is 2.6 nm. The results of UV-Vis spectra of crude extracts of black tea and cuttlefish ink shows the absorption wavelength range in a row of 232-240 nm and 203-207 nm. Large solar cell power supply voltage without soaking, in a room without light and under a halogen lamp is 0.014 Volt and 0.023 Volt. Large voltage solar cells soaked in crude extracts of black tea for 1 hour at room without light and under a halogen lamp is 0.364 Volt and 0.401 Volt. While that is soaked for 2 weeks is 0.113 Volts and 0.18 Volts.